Strategi Penguatan Karakter Pesera Didik Berbasis Nilai Lokal Maja Labo Dahu Pada SMAN 1 Palibelo Bima - Tati Haryati; Rosdiana Rosdiana (Pusat riset dan Inovasi Nasional, 2023)
This study aims to identify and describe strategies for developing the character of students using local values maja labo dahu, at SMAN 1 Palibelo, Bima Regency. The local values of maja labo dahu have become the way of life and the way of life for the people of Bima, from generation to generation. It is appropriate that these values be used as the main basis for supporting character education in schools. % understand the value of maja labo first. The methods used in this research are field studies and surveys or purely descriptive. The number of samples in this study were taken purposively from 10 teachers and 10 students. The data collection technique was carried out through structured interviews and direct field observations. Furthermore, data analysis is done by reduction, interpretation and conclusion. The results of the study found that the implementation of character strengthening went according to the PPK SOP (character education strengthening program) in the school concerned, the difference being the routine Friday morning imtaq activities for 30 minutes before starting learning activities, combining religious material and cultural values locally through oral delivery. Specific strategies used through 3 approaches; parable, training and mentoring.